Expression of emotion in music and vocal communication - Petri Laukka; Anjali Bhatara; Daniel J. Levitin (Frontiers Media SA, 2014)
Two of the most important social skills in humans are the ability to determine the moods of those around us, and to use this to guide our behavior. To accomplish this, we make use of numerous cues. Among the most important are vocal cues from both speech and non-speech sounds. Music is also a reliable method for communicating emotion. It is often present in social situations and can serve to unify a group's mood for ceremonial purposes (funerals, weddings) or general social interactions. Scientists and philosophers have speculated on the origins of music and language, and the possible common bases of emotional expression through music, speech and other vocalizations. They have found increasing evidence of commonalities among them. However, the domains in which researchers investigate these topics do not always overlap or share a common language, so communication between disciplines has been limited. The aim of this Research Topic is to bring together research across multiple disciplines related to the production and perception of emotional cues in music, speech, and non-verbal vocalizations. This includes natural sounds produced by human and non-human primates as well as synthesized sounds. Research methodology includes survey, behavioral, and neuroimaging techniques investigating adults as well as developmental populations, including those with atypical development. Studies using laboratory tasks as well as studies in more naturalistic settings are included.
English
Keywords: Brain processing; Cross-cultural; speech prosody; music perception; Vocalizations; developmental aspects; Emotion Expression; felt emotion; music performance; Acoustic features